Standardization of Cassia spectabilis DC leaves and antimalarial activities of ethyl acetate extract - Wiwied Ekasari; Heny Arwati; Nindya Tresiana Putri; Dewi Hariyani; Rosalia Friska Ananda; Eko Suhartono (Universitas Ahmad Dahlan, 2022)
Cassia spectabilis is one of the Indonesian medicinal plants traditionally used to treat different diseases, including malaria. Quality of a drug derived from plants is also influenced by the quality of its raw materials. Thus, in order to assure the quality of products made from plants, it is necessary to standardize the raw materials and following with the antimalarial activity test. The aim of this study was to standardize the quality of C. spectabilis leaves and to evaluate its antimalarial activities of ethyl acetate extract. The fresh material of C. spectabilis leaves were observed its specific and non-specific parameters. In vitro test was done by using Plasmodium falciparum 3D7. In vivo test was done using 4-day suppressive test method against mice infected with P. berghei for four consecutive days. Heme detoxification inhibitory activity test was carried out using the modified Basilico method. The leaves of C. spectabilis meet the quality requirement for raw material of traditional medicine. The ethyl acetate extract showed in vitro antiplasmodial activity against P. falciparum 3D7 and in vivo antimalarial activity against P. berghei infection with IC50 value of 27.28 Î¼g/mL and ED50 value of 1.74 mg/kg, respectively. The extract also showed heme detoxification inhibitory activity with IC50 value of 0.33Â±0.01 mg/mL. The leaves of C. spectabilis leaves meet the quality requirement and the ethyl acetate extract from standardized C. spectabilis leaves possessed a potential an antimalarial activity which deserves to be further developed.